Diurnal and seasonal differences in cardiopulmonary response to exercise in morning and evening chronotypes - Červená, Kateřina; Spišská, Veronika; Kolář, David; Evansová, Katarína; Skálová, Kateřina; Dostal, Jiří; Vybíral, Stanislav; Bendová, Zdeňka (Chronobiology international, 2021)
Circadian clocks regulate multiple physiological domains from molecular to behavioral levels and adjust bodily physiology to seasonal changes in day length. Circadian regulation of cellular bioenergy and immunity in the cardiovascular and muscle systems may underpin the individual diurnal differences in performance capacity during exercise. Several studies have shown diurnal differences in cardiopulmonary parameters at maximal and submaximal workloads in morning and evening circadian human phenotypes. However, the effect of seasons on these changes was not elucidated. In this study, we recruited subjects with Morningness-Eveningness Questionnaire scores corresponding to morning and evening types. Subjects underwent morning (7:00-9:00) and evening (20:00-22:00) maximal workload spiroergometry in both winter and summer seasons. We analyzed their performance time, anaerobic threshold, heart rate, and respiratory parameters. Our results suggest that evening types manifest diurnal variations in physical performance, particularly in winter. They also have slower heart rate recovery than morning types, irrespective of the time of day or season. Compared to winter, the chronotype effect on the magnitude of morning-evening differences in performance time, maximal heart rate, and anaerobic threshold onset was more significant in summer. Our data are in concordance with previous observations and confirm the difference between morning and evening types in the timing of maximum performance capacity.
Keywords: cirkadiánní rytmus; průzkumy a dotazníky; Surveys and Questionnaires; roční období; Circadian Clocks; Seasons; Circadian Rhythm; cvičení; lidé; cirkadiánní hodiny; Humans; Exercise